Effectiveness of an educational intervention in reducing new international postgraduates’ acculturative stress in Malaysian Public Universities: protocol for a cluster randomized controlled trial - Al-Jaberi, Musheer Abdulwahid; Juni, Muhamad Hanafiah; Shahar, Hayati Kadir; Ismail, Siti Irma Fadhilah; Abdu Saeed, Murad; Lim, Poh Ying (JMIR Publications, 2020)
Background: Universities around the world, including Malaysia, have attracted many international students from different countries. Research has reported that acculturative stress resulting from international students’ attempts to adjust to the cultures of host countries is one of the most challenging issues that affects their lives in general and academic lives in particular. Objective: This study aims to examine the effectiveness of an educational intervention on acculturative stress among new postgraduate international students joining Malaysian public universities. Methods: A cluster randomized controlled trial design with Malaysian public universities as the unit of randomization will be used in this study. Public universities will be randomized in a 1:1 ratio to be either in the intervention (educational program) or control group (waiting list). Participants in the intervention group will receive 7 sessions in 9 hours delivered by an expert in psychology and the researcher. The control group will receive the intervention once the 3-month follow-up evaluation is completed. Results: The data will be analyzed using the generalized estimation equation with a confidence interval value of 95%; significant differences between and within groups are determined as P<.05. The results of the study underlie the effectiveness of educational program in decreasing acculturative stress of new international students and enabling them to cope with a new environment. The results of this study will contribute to previous knowledge of acculturative stress, acculturation, and adjustment of international students. Furthermore, such results are expected to play a role in raising university policy makers’ awareness of their postgraduate international students’ acculturative stress issues and how they can help them avoid such stress and perform well in their academic life. Conclusions: We expect that the intervention group will score significantly lower than the wait-list group on the immediate and 3-month postintervention evaluation of acculturative stress and achieve a higher level of adjustment. Results will have implications for international students, policy makers at universities, the Malaysian Ministry of Higher Education, and future research.